Managerial Mentoring Behaviour and Corporate Vitality in the Nigerian Aviation Sector - Akpotu, Christopher; Konyefa, Rachel (Advances in Social Sciences Research Journal, 2018)
Despite substantial evidence on managerial roles in ensuring performance in work organizations, there is heightened need targeted at exploring and examining managerial behaviour that shapens and strengthen employee capacity that in turn stimulate the needed corporate vitality. This study therefore, examined the empirical link between managerial mentoring and corporate vitality in the Nigerian Hospitality subsector. The study used the questionnaire as the primary instrument for data generation from a sample of 226 respondents. The reliability of the survey instrument was ascertained relying on the Cronbach alpha of 0.78 and benchmarked with the Nunally alpha threshold of 0.7. the data were inferentially analyzed and the findings clearly indicates that a strong positive and significant relationship exist between managerial mentoring dimension of idea clarification empathizing, shared experience and attentiveness and corporate vitality measured with resourcefulness, responsiveness and innovativeness. this is as shown by R=0.74 and it is concluded that managerial mentoring relates with corporate vitality therefore it was recommended amongst others that managers should undertake deliberate and target mentoring initiative that will provide employees with much needed experience and skills that will strengthen the organization for goals.